A stainless steel current collector with protective coating and its preparation method and application

By adding polymer adhesives and protective coatings for stainless steel set flows, the problem of easily corrosion and oxidation during the charging and discharge cycle of stainless steel set flows, and achieve higher corrosion resistance and conductive performance. Extend the life of the battery and reduce the cost.

CN118117097BActive Publication Date: 2025-01-28CHAOWEI POWER GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410256053.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2025-01-28
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

Existing stainless steel current collectors are easily corroded and oxidized during the charge and discharge cycle, affecting the cycle life and safety of the battery.

Method used

The stainless steel sets with a three -layer clipper structure are used. The first protective coating and the second protection coating are composed of polymer adhesives and conductive raw materials. The conductive raw materials account for 80-99%, and the polymer adhesive accounts for 1 to 20%to form a dense conductive protective layer to avoid directly contacting the electrolyte solution from stainless steel foil.

Benefits of technology

It significantly improves the corrosion resistance and conductive performance of stainless steel collecting fluids, prolongs the service life of the collection, reduces the production cost of the battery, and improves the safety and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118117097B_ABST
    Figure CN118117097B_ABST
Patent Text Reader

Abstract

The present invention relates to a stainless steel current collector with a protective coating, a preparation method and an application thereof, and belongs to the technical field of aqueous zinc-manganese batteries, and solves the problem of easy corrosion and oxidation of stainless steel current collectors in the prior art. The present invention discloses a stainless steel current collector, which has a three-layer sandwich structure, which is composed of a first protective coating, a stainless steel foil and a second protective coating from top to bottom; the protective coating is composed of a polymer adhesive and a conductive raw material, wherein the mass percentage of the polymer adhesive is 1-20%, and the mass percentage of the conductive raw material is 80-99%; wherein both the first protective coating and the second protective coating have a dense structure. The stainless steel current collector with a protective coating disclosed in the present invention has the advantages of high oxygen evolution potential, strong acid corrosion resistance, good adhesion with manganese dioxide active materials, high electrochemical redox activity, etc. The electrode sheet and battery cycle performance prepared by the above current collector are significantly improved; the aqueous zinc-manganese battery prepared by the above current collector has a capacity retention rate of 88% after 200 cycles under the conditions of a charge and discharge current density of 100mA / g and a discharge cut-off potential of 0.9V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc-manganese batteries, and in particular to a stainless steel current collector with a protective coating, a preparation method and an application thereof. Background Art

[0002] High-safety, environmentally friendly and low-cost new batteries are important equipment foundations and key technologies for promoting green and clean energy storage and conversion and low-carbon transformation on a large scale in the future, and are an important support for achieving the dual-carbon goals. In recent years, lithium-ion batteries have dominated new energy vehicles in low-carbon travel and transportation vehicles. In the field of electric two-wheeled vehicles, according to statistics, there were 9.7 million lithium-ion battery two-wheeled vehicles in 2020, with a penetration rate of about 23%, which has put tremendous pressure on the market share of lead-acid batteries in this field. Although lead-acid batteries are low-cost and easy to recycle, they have disadvantages such as short cycle life and low energy density. In addition, the new national standard has new requirements for the weight of two-wheeled vehicles, which means that the market will need batteries with higher energy density and better safety as replacements in the future. Lithium-ion batteries have high energy density and good electrical performance, and have great advantages and appeal in the field of two-wheeled and three-wheeled vehicles. However, there are also risks such as high cost and easy fire and explosion of batteries, causing property and casualties. Therefore, the two-wheeled and three-wheeled vehicle markets need to develop a novel small power battery with high safety, high energy, good life and low cost to fill the gap that lead-acid and lithium-ion batteries (lithium manganese oxide batteries) cannot meet the increasing requirements of relative energy density, high safety requirements and low cost requirements.

[0003] In the comparison of various new batteries, aqueous zinc-manganese batteries show strong competitiveness and advantages, because the battery has low cost (close to lead-acid batteries), good cycle life (not less than lithium manganese oxide batteries) and is safe and environmentally friendly. Therefore, the development of aqueous zinc-manganese batteries is of great significance and economic benefits for future applications in electric two-wheeled and three-wheeled vehicles and future energy storage fields. Aqueous zinc-manganese batteries with manganese dioxide as the positive electrode have the advantages of high material gram capacity and low price at low current density. However, the manganese dioxide active material has poor conductivity and unsatisfactory cycle stability.

[0004] In addition, the stability of the positive metal current collector also significantly affects the charge-discharge performance and cycle life of the manganese-based positive electrode. The existing positive current collectors mainly include metal titanium mesh, stainless steel mesh, stainless steel foil and carbon felt / carbon cloth. Metal titanium mesh is expensive and not conducive to large-scale use; although stainless steel mesh and stainless steel foil are cheap, they are easily corroded and oxidized during the charge-discharge cycle; carbon felt has strong corrosion resistance, but its mechanical strength is poor and easy to break, and it is difficult to weld the electrode lugs. Summary of the invention

[0005] In view of the above analysis, the embodiments of the present invention aim to provide a stainless steel current collector with a protective coating and a preparation method and application thereof, so as to solve the problem that the existing stainless steel current collector is easily corroded and oxidized during the charge and discharge cycle.

[0006] The invention discloses a stainless steel current collector, which has a three-layer sandwich structure, which comprises a first protective coating, a stainless steel foil and a second protective coating from top to bottom; the first protective coating and the second protective coating are composed of a polymer adhesive and a conductive raw material, wherein the mass percentage of the polymer adhesive is 1-20%, and the mass percentage of the conductive raw material is 80-99%; wherein the first protective coating and the second protective coating both have a dense structure.

[0007] Preferably, the mass percentage of the polymer adhesive is 5-15%, and the mass percentage of the conductive raw material is 85-95%.

[0008] Specifically, the polymer adhesive is one of CMC, PVA or PVDF.

[0009] Specifically, the conductive raw material is one of graphite, graphene or carbon nanotubes.

[0010] Specifically, the thickness of the first protective coating and / or the second protective coating is 20-50 μm; the porosity of the first protective coating and the second protective coating is ≤5%.

[0011] The present invention also discloses a method for preparing the stainless steel current collector, comprising the following steps:

[0012] S1: weighing a polymer adhesive and a conductive raw material according to a preset ratio, and mixing and stirring the adhesive and an appropriate amount of solvent to obtain an adhesive solution;

[0013] S2: adding the conductive raw material to the binder solution, stirring and ball milling to obtain a mixed slurry, and degassing the mixed slurry for later use;

[0014] S3: Degreasing, cleaning and drying the stainless steel foil for later use;

[0015] S4: coating the degassed mixed slurry on both sides of the stainless steel foil, and drying to obtain a stainless steel current collector having a first protective coating and a second protective coating.

[0016] The invention also discloses an electrode sheet, which is made from the stainless steel current collector.

[0017] Specifically, the electrode sheet is composed of a stainless steel current collector and active materials, which are respectively a first active material layer, a stainless steel current collector, and a second active material layer from top to bottom; the specific composition of the active material is 80-82% manganese dioxide, 5-10% first conductive agent, 7-10% second conductive agent, and 3-5% binder in terms of mass percentage.

[0018] Specifically, the first conductive agent is graphene or carbon nanotube; the second conductive agent is artificial or natural graphite; and the binder is CMC or PTFE.

[0019] The present invention also discloses a method for preparing the electrode sheet, comprising the following steps:

[0020] S21: weighing or measuring manganese dioxide powder, a first conductive agent, a second conductive agent and a binder according to a preset ratio, preparing a first conductive agent aqueous solution, and sieving the manganese dioxide powder and mixing and stirring the first conductive agent aqueous solution, and then performing ultrasonic crushing and mixing treatment;

[0021] S22: preparing a binder solution, adding the second conductive agent and the binder solution to the mixed solution obtained in S21, stirring evenly and then ball milling to obtain a mixed slurry and degassing;

[0022] S23: coating the mixed slurry on both sides of a stainless steel current collector having a protective layer and drying it, and rolling it to a desired thickness to obtain an electrode sheet.

[0023] The invention also discloses a battery, which is made from the electrode sheet.

[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0025] 1. The stainless steel current collector with a protective coating provided by the present invention has a high oxygen evolution potential and good corrosion resistance.

[0026] For example, the anodic oxidation current of the current collector at 1.92 V (relative to the zinc electrode) is only 0.1 mA / cm 2 At the same anodization current (0.1mA / cm 2 ) conditions, the potential of the coated stainless steel is about 80 mV higher than that of the uncoated stainless steel, indicating that the anodic process has a strong antioxidant ability and good resistance to oxidative corrosion.

[0027] Since the protective coating disclosed in the present invention has a dense structure, a porosity of no more than 5% and good conductivity, it can effectively separate the current collector / stainless steel foil from the electrolyte while ensuring the carrier / electron transmission efficiency, thereby greatly improving the corrosion resistance of the current collector and its service life. In particular, when PVDF is selected as the binder, the protective coating will also have a certain hydrophobicity, further improving the corrosion resistance.

[0028] 2. The electrode sheet provided by the present invention has high electrochemical redox reaction activity. Experimental data (cyclic voltammetry curve) show that the electrode with a protective coating has a higher redox reaction peak current and a larger peak area for the active substance manganese dioxide than the uncoated electrode, indicating that the manufactured coated electrode sheet has high electrochemical reaction activity and good reversibility.

[0029] 3. The stainless steel current collector, electrode sheet and battery preparation method provided by the present invention have simple processes and can adopt mature lithium-ion battery production equipment. However, the entire manufacturing process does not require an inert gas protection device, does not require strict control of humidity and harsh conditions of extremely low oxygen content, has low manufacturing cost, and the required raw materials are abundant, easy to obtain, and low in cost, which is suitable for large-scale manufacturing and wide promotion.

[0030] 4. The aqueous zinc-manganese battery provided by the present invention has high cost performance, and its cost per watt-hour (0.35 to 0.45 yuan) is comparable to that of traditional lead-acid batteries, but its mass-to-energy density (60 watt-hours / kg) is higher than that of lead-acid batteries (40 to 50 watt-hours / kg), has good cycle stability and is free of heavy metal lead pollution.

[0031] 5. The aqueous zinc-manganese battery provided by the present invention is highly safe and will not burn or explode. The battery also does not contain heavy metals and organic media, is environmentally friendly, and is a green battery.

[0032] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0034] Figure 1 Schematic diagram of the electrode sheet structure;

[0035] Figure 2The linear polarization (LSV) curves of the electrodes of Examples 1 to 5 and the comparative example are shown;

[0036] Figure 3 XRD powder diffraction pattern of manganese dioxide (CuKα );

[0037] Figure 4 1 is a cyclic voltammetry (CV) curve of Example 1, Example 5 and the comparative example electrode;

[0038] FIG. 5( a ) and FIG. 5( b ) are scanning electron microscope (SEM) images of the surface of the manganese dioxide electrode in Example 1, wherein:

[0039] Figure 5(a) is a scanning electron microscope image at 2200 times magnification;

[0040] FIG5( b ) is a partially enlarged electron microscope image of FIG5( a );

[0041] FIG6( a ) is a graph showing the relationship between the positive electrode constant current discharge capacity and the number of cycles under constant current charging conditions and the corresponding charging efficiency curve of the manganese dioxide electrode in Example 1;

[0042] FIG6( b ) is a graph showing discharge curves at the 1st, 10th and 210th times;

[0043] Figure 7 The curve showing the relationship between the positive electrode constant current discharge capacity and the number of cycles under the mixed charging conditions of constant current and constant voltage in Example 3;

[0044] Figure 8 The curve showing the relationship between the positive electrode constant current discharge capacity and the number of cycles under the mixed charging conditions of constant current and constant voltage in Example 4;

[0045] Fig. 9 This is the relationship curve between the positive electrode constant current discharge capacity and the number of cycles of the manganese dioxide electrode in the comparative example under the mixed charging conditions of constant current and constant voltage. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0047] The invention discloses a stainless steel current collector, which has a three-layer sandwich structure, which comprises a first protective coating, a stainless steel foil and a second protective coating from top to bottom; the first protective coating and the second protective coating are composed of a polymer adhesive and a conductive raw material, wherein the mass percentage of the polymer adhesive is 1-20%, and the mass percentage of the conductive raw material is 80-99%; wherein both the first protective coating and the second protective coating have a dense structure.

[0048] The first / second protective coating ensures the conductivity of the stainless steel current collector while preventing the stainless steel foil from directly contacting the electrolyte solution over a large area (the protective coating has a dense structure, and the electrolyte solution is not easy to penetrate / permeate the protective coating and directly contact the stainless steel foil), thereby preventing or delaying the occurrence of oxygen evolution, improving the corrosion resistance of the stainless steel current collector in a slightly acidic medium environment, and helping to increase the oxygen evolution potential in the later stage of charging, thereby improving the charging efficiency.

[0049] The amount of adhesive added should not be too little, so as to avoid insufficient adhesion of the protective coating, resulting in the coating falling off; the amount of adhesive added should not be too much, so as to avoid insufficient conductivity. According to the actual implementation results, since the protective coating greatly delays the corrosion of the stainless steel foil, it is objectively equivalent to improving the long-term conductivity of the current collector (the initial conductivity does not change significantly, but the current collector / stainless steel foil in the prior art will gradually corrode during service, and the conductivity will gradually decrease).

[0050] Preferably, the mass percentage of the polymer adhesive is 5-15%, and the mass percentage of the conductive raw material is 85-95%.

[0051] Specifically, the polymer adhesive is one of CMC, PVA or PVDF, preferably PVDF. Since PVDF is hydrophobic, the formed protective layer will also have certain hydrophobic properties, further reducing the possibility of direct contact between the stainless steel foil and the electrolyte solution over a large area.

[0052] Specifically, the conductive raw material is one of graphite, graphene or carbon nanotubes, and the above conductive raw materials can effectively improve the conductive performance of the protective coating.

[0053] Specifically, the thickness of the first protective coating or the second protective coating is 20 to 50 μm, the porosity of the first protective coating and the second protective coating is ≤5%, and the porosity is calculated to be 4.1% by analyzing the coating SEM image (protective coating in Example 1) using Image Pro Plius. The results show that the surface coating is relatively dense. The realization of the above-mentioned low porosity is the result of the combined effect of material selection and process. In terms of material selection, the conductive materials, adhesives, etc. used in the present invention can maintain or even exert better performance at small particle sizes; in terms of the protective coating preparation process, the present invention obtains conductive raw materials and adhesives with small particle sizes (5 to 15 microns) through a ball milling stirring process (step S2), thereby reducing the gaps caused by irregular shapes and excessive particle sizes in the later material accumulation, and further removes the gas mixed in the preparation process through a degassing process, thereby further reducing the porosity; before the protective coating is applied, the surface of the stainless steel foil is pretreated, which also helps to reduce structural gaps / voids that may be generated at the interface; the drying process adopts a slow drying process to ensure the moisture drying effect while achieving gentle drying as much as possible, thereby avoiding cracking of the coating and helping to obtain a more delicate and low-porosity protective coating.

[0054] The non-hydrophilic surface coating will help prevent electrolyte penetration, effectively isolate the base stainless steel from the electrolyte, and prevent large-area contact with the electrolyte. The coating should not be too thin or too thick. If the coating is too thin, the protective effect will be poor; if the coating is too thick, it will affect the efficiency of electron passage and increase the inactive mass of the electrode, and it will also cause a waste of resources.

[0055] Specifically, the thickness of the stainless steel foil is 6 to 50 μm. In actual implementation, the smaller the thickness of the stainless steel foil, the more conducive it is to improving the battery mass-to-energy density; however, too thin a thickness may cause it to curl or wrinkle easily, affecting the coating quality and electrode performance.

[0056] The present invention also discloses a method for preparing the stainless steel current collector, comprising the following steps:

[0057] S1: weighing a polymer adhesive and a conductive raw material according to a preset ratio, and mixing and stirring the adhesive and an appropriate amount of solvent to obtain an adhesive solution;

[0058] S2: adding the conductive raw material to the binder solution, stirring and ball milling to obtain a mixed slurry, and degassing the mixed slurry for later use;

[0059] S3: Degreasing, cleaning and drying the stainless steel foil for later use;

[0060] S4: Use a coater to coat the degassed mixed slurry on both sides of the stainless steel foil, and after drying, obtain a stainless steel current collector having a first protective coating and a second protective coating.

[0061] Specifically, in step S1, different solvents should be selected according to the type of polymer adhesive. The corresponding solvent for PVDF is N-methylpyrrolidone (NMP), and the corresponding solvents for PVA and CMC are water.

[0062] Specifically, the mass ratio of PVDF adhesive to solvent is 3-10:90-97; the mass ratio of PVA adhesive to solvent is 3-8:92-97; the mass ratio of CMC adhesive to solvent is 1-3:99-97. The amount of solvent added should not be too low, otherwise the bonding strength is insufficient and the material is easy to fall off; the amount of solvent added should not be too high, otherwise the conductive performance will be reduced and the internal resistance will be increased. Too much addition of adhesive is also not conducive to the uniformity of subsequent coating.

[0063] Specifically, magnetic stirring may be used in step S2, and the stirring time is 10 to 30 hours.

[0064] Specifically, the specific parameters of the ball milling in step S2 are a ball-to-material ratio of 10:1, a rotation speed of 200-300 RPM, and a time of 2-6 hours, so that the adhesive and the conductive material are fully mixed and evenly ground into particles of smaller size, with a particle size distribution of about 5-15 microns, which helps to form a dense protective coating later.

[0065] Specifically, the specific operation of degassing in step S2 is to place the slurry in a low-pressure degassing tank for degassing treatment, so as to prevent pinholes from forming in the coating and facilitate the formation of a uniform and dense coating.

[0066] Specifically, the specific operation of step S3 is to soak the stainless steel foil in a sodium carbonate solution at 60-70°C overnight to remove oil, then rinse it with clean water and ultrasonically clean it in an acetone solution for 5-10 minutes, then rinse it with clean water and blow it dry for later use. This step can effectively remove the oxide layer and other impurities of the stainless steel foil, which helps to improve the adhesion of the protective coating; and this process helps to improve the glossiness of the surface of the stainless steel foil, which is conducive to forming a dense and firm protective coating.

[0067] Specifically, the specific operation of drying in step S4 is to slowly dry the semi-finished stainless steel current collector under an infrared lamp and dry it in a vacuum oven at 100-150 degrees to solidify the protective coating. The temperature of the entire drying process should not be too high to avoid cracking of the coating, so as to ensure the firmness and density of the protective coating.

[0068] The invention also discloses an electrode sheet, which is made from the stainless steel current collector.

[0069] Specifically, the electrode sheet is composed of a stainless steel current collector and active materials, which are respectively a first active material layer, a stainless steel current collector, and a second active material layer from top to bottom; the specific composition of the active material is 80-82% manganese dioxide, 5-10% first conductive agent, 7-10% second conductive agent, and 3-5% binder in terms of mass percentage.

[0070] Specifically, the first conductive agent is graphene or carbon nanotube; the second conductive agent is artificial or natural graphite; and the binder is CMC or PTFE.

[0071] Manganese dioxide: an active substance that participates in electrochemical redox reactions; increasing the content of active substances in the electrode will increase the absolute electrochemical capacity of the electrode. However, if the content is too high, the charge and discharge utilization rate will be reduced, which is not conducive to the specific energy density of the battery.

[0072] First conductive agent: Graphene or carbon nanotubes have very high electronic conductivity. After adding, it is not only beneficial to improve the electronic conductivity and utilization rate of manganese dioxide active material, but also improve the cycle life.

[0073] Second conductive agent: Graphite has low cost and a granular structure with excellent conductivity. After being added, it is beneficial to form a continuous conductive network with the first conductive agent in the electrode active material and improve the penetration ability of the electrolyte in the electrode material.

[0074] Binder: The binder dissolves in the solvent to form a colloidal solution, which has excellent dispersing and thickening effects. It can suspend the active material and conductive additive well in the colloidal solution to form a slurry for easy electrode coating. In addition, the binder also prevents the active material from falling off the current collector, maintains the integrity of the electrode during charging and discharging, and improves the cycle stability of the electrode. The binder is a non-conductive substance, so its content should be as low as possible under the premise of electrode preparation and maintaining the integrity of the electrode during charging and discharging.

[0075] Specifically, the thickness of the active material layer (single layer) can be adjusted according to actual needs.

[0076] The present invention also discloses a method for preparing the electrode sheet, comprising the following steps:

[0077] S21: weighing or measuring manganese dioxide powder, a first conductive agent, a second conductive agent and a binder according to a preset ratio, preparing a first conductive agent aqueous solution, and sieving the manganese dioxide powder and mixing and stirring the first conductive agent aqueous solution, and then performing ultrasonic crushing and mixing treatment;

[0078] S22: preparing a binder solution, adding the second conductive agent and the binder solution to the mixed solution obtained in S21, stirring evenly and then ball milling to obtain a mixed slurry and degassing;

[0079] S23: coating the mixed slurry on both sides of a stainless steel current collector having a protective layer and drying it, and rolling it to a desired thickness to obtain an electrode sheet.

[0080] Specifically, in step S21, the manganese dioxide powder is sieved through a 400-mesh sieve, and the sieved powder with a small particle size is taken to continue the subsequent operation.

[0081] Specifically, the mass concentration of the first conductive agent aqueous solution is 1-5%.

[0082] Specifically, the specific parameters of the ultrasonic crushing in step S21 are a frequency of 50 Hz, intermittent ultrasound working for 3 to 10 seconds and stopping for 1 to 5 seconds, and the total ultrasonic working time is 10 to 60 minutes. The ultrasonic crushing of the mixture is beneficial to partially or completely crushing the flaky graphene or the long strips of carbon nanotubes, so that the manganese dioxide and the first conductive agent are more evenly mixed.

[0083] Specifically, the specific operation of ball milling in step S22 is: pour the mixed slurry into a ball milling jar, add ball milling ceramic balls, add the ball-to-material ratio (mass ratio) of 10:1, and then ball mill at a speed of 200-300RPM for 6-12 hours.

[0084] Specifically, the role and benefit of adding the first conductive agent and the second conductive agent in batches in steps S21 and S22 is to first utilize the high specific surface area and excellent conductivity of graphene or carbon nanotubes, add them evenly and disperse them so that they are fully mixed with manganese dioxide, which is beneficial to improving the electronic conductivity of manganese dioxide, reducing the electrochemical reaction resistance, and improving the electrochemical performance of manganese dioxide.

[0085] Then, a second conductive agent with a particle size of no more than 15 microns is added to fill the three-dimensional structural space gap formed by the mixture of the first conductive agent flaky graphene or carbon nanotubes and granular manganese dioxide, and work synergistically with the first conductive agent to further improve the electrical contact between the active material and the conductive agent, increase the electron transfer rate, and improve the electrode performance.

[0086] Specifically, the specific operation of drying in step S23 is: placing the semi-finished electrode sheet at room temperature for a period of time to allow it to slowly dry and then drying it in an oven at 80° C. to prevent the active material layer from cracking.

[0087] Specifically, the electrode sheet is spot welded to the electrode lug and used as the positive electrode.

[0088] The invention also discloses a battery, which comprises the electrode sheet.

[0089] For example, a zinc sheet is used as the negative electrode, and a film made of a grafted polypropylene film and a non-woven fabric is used as a separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 is used as the electrolyte (pH value is 4), and a square battery is assembled.

[0090] Example 1

[0091] Preparation of stainless steel current collector:

[0092] 3.6 g of PVDF was weighed and added to 96 mL of N-methylpyrrolidone (NMP) solvent, and the mixture was thoroughly mixed to obtain a PVDF solution. 57 g of artificial graphite was added to the PVDF solution, magnetically stirred for 10 h and ball milled, with the ball-to-material ratio of 10:1, ball milling time of 6 h, and rotation speed of 300 RPM to obtain a mixed slurry, which was placed in a low-pressure degassing tank for degassing and standby use.

[0093] Clean the stainless steel foil with hot water containing a small amount of soda to remove oil stains, then ultrasonically clean it in acetone solution for 8 minutes, wash it with clean water several times and blow dry it for later use.

[0094] A stainless steel foil of 100*200 mm and 50 μm thick was cut, and the slurry was evenly coated on the front and back sides of the steel foil with a coater with controllable thickness. It was first slowly dried at room temperature and then under an infrared lamp and finally dried in a vacuum oven at 120 degrees to form a dense conductive protective layer with a porosity of 4.1% and a thickness of about 50 μm, thereby obtaining a stainless steel current collector with a protective coating.

[0095] A slightly acidic electrolyte containing 1M MnSO4+1.5M ZnSO4 and a small amount of H2SO4 was prepared, and its pH value was 4. The linear polarization curve (LSV) test of the above stainless steel current collector was carried out, and the results are as follows Figure 2 As shown, the scanning rate is 2mV / S, and the initial oxygen evolution potential is about 1.92V. This shows that after the surface of the stainless steel foil is coated with non-hydrophilic PVDF and graphite, the anti-oxidation corrosion ability of the stainless steel foil (current collector) in a slightly acidic electrolyte environment is significantly improved and oxygen evolution is inhibited in the later stage of charging.

[0096] Preparation of electrodes and batteries:

[0097] According to the technical solution of the present invention, a manganese dioxide electrode slurry containing 82% manganese dioxide, 5% graphene, 10% artificial graphite and 3% CMC is prepared in terms of mass percentage.

[0098] The above-mentioned stainless steel current collector with protective coating having a size of 30×50 mm is taken for use.

[0099] The 400-mesh manganese dioxide powder was tested by XRD, and its phase was mainly alpha phase structure (such as Figure 34.1g of manganese dioxide powder was added to 10.4g of a graphene aqueous phase mixture containing 2.4% by mass concentration, and ultrasonically mixed for 30 minutes, and 0.5g of artificial graphite was added for mechanical stirring and mixing, and after stirring for 16 hours, 10g of a CMC binder containing 1.5% by mass concentration was added, and then ball milled for 6 hours (ball-to-material ratio 10:1, speed 300 rpm), the slurry was taken out and degassed, and then the slurry was coated on the above-mentioned stainless steel current collector, dried at room temperature for several hours and dried in an oven at 80 degrees, and then rolled with a biaxial roller to the required electrode thickness of 0.1-0.2 mm, and the electrode ears were spot welded; the manganese dioxide active material loading was measured to be 3.0mg / cm 2 , the total thickness of the electrode is about 100 microns.

[0100] Electron microscopic observation of the electrode surface shows that in addition to bulk manganese dioxide, there are also flake graphene and small particles of artificial graphite. The manganese dioxide particles on the electrode surface are evenly distributed, and the electron microscopic photos are shown in Figure 5 (a) and Figure 5 (b).

[0101] Battery preparation and testing:

[0102] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0103] Test conditions: charge and discharge battery density is 100mA / g, discharge cut-off potential is 0.9V.

[0104] FIG6(a) is a cycle stability curve of the assembled battery of this embodiment under constant current charge and discharge conditions. The results show that the initial discharge capacity of manganese dioxide is about 210 mAh / g, and the capacity retention rate after 200 cycles is 88%, which has high cycle stability, and the discharge capacity is about 185 mAh / g. FIG6(b) is a discharge curve at the 1st, 10th and 210th times.

[0105] Example 2

[0106] Preparation of stainless steel current collector:

[0107] Weigh 0.3g PVDF, add it to 6mL N-methylpyrrolidone (NMP) solvent, and mix thoroughly to obtain PVDF solution. Add 142g of graphene with a mass concentration of 3.0% to the PVDF solution, stir magnetically for 15h and ball mill, the ball milling parameters are ball-to-material ratio 10:1, ball milling time 4h, rotation speed 250RPM, to obtain a mixed slurry, and place the mixed slurry in a low-pressure degassing tank for degassing and standby.

[0108] The stainless steel foil current collector was cleaned with hot water containing a small amount of soda to remove oil stains, then ultrasonically cleaned in an acetone solution for 10 minutes, washed with clean water several times and blown dry for later use.

[0109] A stainless steel foil of 100*200 mm and 30 μm thick was cut, and the slurry was evenly coated on the front and back sides of the steel foil with a coater with controllable thickness. It was first slowly dried at room temperature and then under an infrared lamp and finally dried in a vacuum oven at 120 degrees to form a dense conductive protective layer with a thickness of about 40 μm, thereby obtaining a stainless steel current collector with a protective coating.

[0110] A slightly acidic electrolyte containing 1M MnSO4+1.5M ZnSO4 and a small amount of H2SO4 was prepared, and its pH value was 4. The linear polarization curve (LSV) test of the above stainless steel current collector was carried out, and the results are as follows Figure 2 As shown, the scan rate is 2mV / S, and the initial oxygen evolution potential is about 1.86V. Compared with the uncoated stainless steel foil, the surface of the stainless steel foil coated with PVDF and graphene improves the anti-oxidation corrosion ability of the stainless steel foil (current collector) in a slightly acidic electrolyte environment and inhibits oxygen evolution in the later stage of charging.

[0111] Preparation of electrodes and batteries:

[0112] According to the technical solution of the present invention, a manganese dioxide electrode slurry containing 80% manganese dioxide, 7% graphene, 9% artificial graphite and 4% CMC is prepared in terms of mass percentage.

[0113] The above-mentioned stainless steel current collector with protective coating having a size of 30×50 mm is taken for use.

[0114] The 400-mesh manganese dioxide powder was tested by XRD, and its physical phase was mainly alpha phase structure, such as Figure 3 As shown. Take 3.9g of manganese dioxide powder and add 11.36g of a water phase mixture containing 3.0% graphene by mass concentration, and mix it ultrasonically for 30 minutes. Add 0.44g of artificial graphite for mechanical stirring and mixing. After stirring for 10 hours, add 13g of CMC adhesive containing 1.5% by mass concentration, and then ball mill for 6 hours (ball-to-material ratio 10:1, speed 300 rpm). After taking out the slurry and degassing, the slurry is coated on the above-mentioned stainless steel current collector, dried at room temperature for several hours and dried in an oven at 80 degrees, and then rolled with a biaxial roller to the required electrode thickness of 0.10 mm, and the electrode ears are spot welded; the manganese dioxide active material loading is measured to be 3.1mg / cm 2 , the total thickness of the electrode is about 100 microns.

[0115] Battery preparation and testing:

[0116] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0117] Test conditions: the battery density is 100mA / g, and the discharge cut-off potential is 0.9V. The assembled battery was tested under constant current charge and discharge conditions and the cycle stability curve was determined. The results showed that the initial discharge capacity of manganese dioxide was about 239 mAh / g, but the initial capacity decayed quickly, and dropped to 150-160 mAh / g after 10 cycles. The discharge performance was relatively stable afterwards, and the discharge capacity decreased slowly with the increase of the number of cycles.

[0118] Example 3

[0119] Preparation of stainless steel current collector:

[0120] Weigh 0.671g CMC, add it to 45mL water, and mix thoroughly to obtain CMC solution. Add 5.43g artificial graphite to the CMC solution, stir magnetically for 20h and ball mill, the ball milling parameters are ball to material ratio 10:1, ball milling time 4h, speed 250RPM, to obtain mixed slurry, and place the mixed slurry in a low-pressure degassing tank for degassing and standby.

[0121] The stainless steel foil current collector was cleaned with hot water containing a small amount of soda to remove oil stains, then ultrasonically cleaned in an acetone solution for 6 minutes, washed with clean water several times and blown dry for later use.

[0122] A stainless steel foil of 100*200 mm and 50 μm thick was cut, and the slurry was evenly coated on the front and back sides of the steel foil with a coater with controllable thickness. It was slowly dried in a step-by-step manner at room temperature under an infrared lamp and dried in a vacuum oven at 130 degrees to form a dense conductive protective layer with a thickness of about 36 μm, thereby obtaining a stainless steel current collector with a protective coating.

[0123] A slightly acidic electrolyte containing 1M MnSO4+1.5M ZnSO4 and a small amount of H2SO4 was prepared, and its pH value was 4. The linear polarization curve (LSV) test of the above stainless steel current collector was carried out, and the results are as follows Figure 2 As shown, the scan rate is 2mV / S, and the initial oxygen evolution potential is about 1.88V. Compared with the uncoated stainless steel foil, after coating with CMC and graphite, the surface of the stainless steel foil has improved its anti-oxidation corrosion ability and inhibited oxygen evolution in the later stage of charging. However, compared with the stainless steel foil current collector coated with PVDF and graphite, the initial oxygen evolution potential is reduced.

[0124] Preparation of electrodes and batteries:

[0125] According to the technical solution of the present invention, a manganese dioxide electrode slurry containing 81% manganese dioxide, 6% graphene, 8% artificial graphite and 5% CMC is prepared in terms of mass percentage.

[0126] The above-mentioned stainless steel current collector with protective coating having a size of 30×50 mm is taken for use.

[0127] The 400-mesh manganese dioxide powder was tested by XRD, and its physical phase was mainly alpha phase structure, such as Figure 3 As shown. Take 3.0g of manganese dioxide powder and add 11.11g of a water phase mixture containing 2.0% graphene by mass concentration, and mix it ultrasonically for 30 minutes, add 0.296g of artificial graphite for mechanical stirring and mixing, stir for 12 hours, add 12.35g of CMC adhesive containing 1.5% by mass concentration, and then ball mill for 8 hours (ball-to-material ratio 10:1, speed 300 rpm), take out the slurry and degas, then coat the slurry on the above-mentioned stainless steel current collector, dry it at room temperature for several hours and dry it in an oven at 80 degrees, then use a biaxial roller press to roll it to the required electrode thickness of about 0.1 mm, and spot weld the electrode ears; the manganese dioxide active material loading is measured to be 3.05mg / cm 2 , the total thickness of the electrode is 104 microns.

[0128] Battery preparation and testing:

[0129] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0130] Test conditions: charge and discharge battery density is 100mA / g, discharge cut-off potential is 0.9V.

[0131] Figure 7 This is the battery cycle stability curve obtained by testing under constant current charge and discharge conditions in this embodiment. The initial cycle shows a higher discharge capacity. After more than ten cycles, the discharge capacity decreases and tends to be stable. The discharge capacity of manganese dioxide is 150-175 mA·h / g, and the cycle stability is good.

[0132] Example 4

[0133] Preparation of stainless steel current collector:

[0134] Weigh 0.152g CMC, add it to 10mL water, and mix thoroughly to obtain CMC solution. Add 42.4g of graphene aqueous phase mixture with a mass concentration of 2.4% to the CMC solution, stir magnetically for 15h and ball mill, the ball milling parameters are ball to material ratio 10:1, ball milling time 6h, rotation speed 250RPM, to obtain a mixed slurry, and place the mixed slurry in a low-pressure degassing tank for degassing and standby.

[0135] The stainless steel foil current collector was cleaned with hot water containing a small amount of soda to remove oil stains, then ultrasonically cleaned in an acetone solution for 10 minutes, washed with clean water several times and blown dry for later use.

[0136] A stainless steel foil of 100*200 mm and 50 μm thick was cut, and the slurry was evenly coated on the front and back sides of the steel foil with a coater with controllable thickness. It was slowly dried in a step-by-step manner at room temperature under an infrared lamp and dried in a vacuum oven at 120 degrees to form a dense conductive protective layer with a thickness of about 30 μm, thereby obtaining a stainless steel current collector with a protective coating.

[0137] A slightly acidic electrolyte containing 1M MnSO4+1.5M ZnSO4 and a small amount of H2SO4 was prepared, and its pH value was 4. The linear polarization curve (LSV) test of the above stainless steel current collector was carried out, and the results are as follows Figure 2 As shown, the scan rate is 2mV / S, and the initial oxygen evolution potential is about 1.84V. Compared with the uncoated stainless steel foil, after coating with CMC and graphene, the surface of the stainless steel foil has enhanced the ability to inhibit oxygen evolution. However, compared with the stainless steel foil current collector coated with PVDF and graphene, the initial oxygen evolution potential is reduced. This shows that the effect of inhibiting oxygen evolution after the stainless steel foil surface is coated with CMC and graphene is not as good as that of PVDF. This may be related to the fact that PVDF is a non-hydrophilic substance, while CMC is a hydrophilic substance.

[0138] Preparation of electrodes and batteries:

[0139] According to the technical solution of the present invention, a manganese dioxide electrode slurry containing 82% manganese dioxide, 7% graphene, 7% artificial graphite and 4% CMC is prepared in terms of mass percentage.

[0140] The above-mentioned stainless steel current collector with protective coating having a size of 30×50 mm is taken for use.

[0141] The 400-mesh manganese dioxide powder was tested by XRD, and its physical phase was mainly alpha phase structure, such as Figure 3As shown. Take 3.3g of manganese dioxide powder and add 11.74g of a graphene aqueous phase mixture containing a mass concentration of 2.4%, and ultrasonically mix for 30 minutes, add 0.282g of artificial graphite for mechanical stirring and mixing, stir for 16 hours, add 10.73g of a CMC binder containing a mass concentration of 1.5%, and then ball mill for 8 hours (ball-to-material ratio 10:1, speed 300 rpm), take out the slurry and degas, then coat the slurry on the above-mentioned stainless steel current collector, dry it at room temperature for several hours and dry it in an oven at 80 degrees, and then use a biaxial roller press to roll it to the required electrode thickness of about 0.1 mm, and spot weld the electrode ears; the manganese dioxide active material loading is measured to be 2.95mg / cm 2 , the total thickness of the electrode is 100 microns.

[0142] Battery preparation and testing:

[0143] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0144] Test conditions: charge and discharge battery density is 100mA / g, discharge cut-off potential is 0.9V.

[0145] Figure 8 This is the battery cycle stability curve obtained under constant current charge and discharge conditions. It can be seen that the use of graphene has a large initial discharge capacity of 275 mAh / g, but as the number of cycles increases, the initial high discharge capacity gradually decreases. After 80 cycles, the discharge capacity is stable in the range of 100-120 mAh / g. Although the stable discharge capacity is not as high as that of Examples 1 and 2, it is obviously higher than that of Example 1. Fig. 9 The result is good.

[0146] Example 5

[0147] Preparation of stainless steel current collector:

[0148] 1.75 g of PVA was weighed and added to 56 mL of water, and the mixture was thoroughly mixed to obtain a PVA solution. 7.97 g of artificial graphite was added to the PVA solution, magnetically stirred for 10 h, and ball milled. The ball milling parameters were a ball-to-material ratio of 10:1, a ball milling time of 2 h, and a rotation speed of 300 RPM to obtain a mixed slurry. The mixed slurry was placed in a low-pressure degassing tank for degassing and then used.

[0149] The stainless steel foil current collector was cleaned with hot water containing a small amount of soda to remove oil stains, then ultrasonically cleaned in an acetone solution for 10 minutes, washed with clean water several times and blown dry for later use.

[0150] A stainless steel foil of 100*200 mm and 50 μm thick was cut, and the slurry was evenly coated on the front and back sides of the steel foil with a coater with controllable thickness. It was slowly dried in a step-by-step manner at room temperature under an infrared lamp and dried in a vacuum oven at 120 degrees to form a dense conductive protective layer with a thickness of about 25 μm, thereby obtaining a stainless steel current collector with a protective coating.

[0151] A slightly acidic electrolyte containing 1M MnSO4+1.5M ZnSO4 and a small amount of H2SO4 was prepared, and its pH value was 4. The linear polarization curve (LSV) test of the above stainless steel current collector was carried out, and the results are as follows Figure 2 As shown, the scanning speed is 2mV / S, and the initial oxygen evolution potential is about 1.84V. After coating with PVA and graphite, the surface of the stainless steel foil does not significantly improve the potential to inhibit oxygen evolution. However, the stainless steel substrate is protected and the electrochemical properties of the electrode are improved. Compared with the uncoated stainless steel foil electrode, the initial discharge capacity and stability of the electrode after coating with PVA and graphite are significantly improved (see Figure 8 and Fig. 9 ). The cyclic voltammetry (CV) test of the electrode also showed that ( Figure 4 ) After the stainless steel electrode surface was coated with PVA, there were obvious oxidation and reduction peaks of manganese dioxide, while the uncoated electrode had no obvious oxidation and reduction peaks in the CV curve. This shows that the PVA coating layer improved the electrochemical activity of manganese dioxide electrode during charge and discharge.

[0152] Preparation of electrodes and batteries:

[0153] According to the technical solution of the present invention, a manganese dioxide electrode slurry containing 80% manganese dioxide, 8% graphene, 7% artificial graphite and 5% CMC is prepared in terms of mass percentage.

[0154] The above-mentioned stainless steel current collector with protective coating having a size of 30×50 mm is taken for use.

[0155] The 400-mesh manganese dioxide powder was tested by XRD, and its physical phase was mainly alpha phase structure, such as Figure 3 As shown. Take 2.8g of manganese dioxide powder and add 10.00g of a graphene aqueous phase mixture containing a mass concentration of 2.8%, and ultrasonically mix for 30 minutes, add 0.245g of artificial graphite for mechanical stirring and mixing, stir for 16 hours, add 11.67g of CMC adhesive containing a mass concentration of 1.5%, and then ball mill for 6 hours (ball-to-material ratio 10:1, speed 300 rpm), take out the slurry and degas, then coat the slurry on the above-mentioned stainless steel current collector, dry it at room temperature for several hours and dry it in an oven at 80 degrees, and then roll it with a biaxial roller to the required electrode thickness of about 0.1 mm, and spot weld the electrode ears; the manganese dioxide active material loading is measured to be 3.0mg / cm 2, the total thickness of the electrode is 100 microns.

[0156] Battery preparation and testing:

[0157] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0158] Test conditions: charge and discharge battery density is 100mA / g, discharge cut-off potential is 0.9V.

[0159] The initial discharge capacity is 90mAh / g, and the discharge capacity after 100 cycles is 70mAh / g.

[0160] Figure 4 1 and 2 are cyclic voltammetry (CV) curves of electrode tests, which are comparison curves of stainless steel foil electrodes coated with PVDF (Example 1) and PVA adhesive (Example 5) mixed with graphite and uncoated stainless steel foil.

[0161] The results show that after the stainless steel electrode surface is coated with PVDF or PVA, there are obvious oxidation and reduction peaks of manganese dioxide, while the uncoated electrode has no oxidation and reduction peaks on the CV curve. This shows that the coating of the conductive protective layer improves the electrochemical activity of manganese dioxide electrode charging and discharging. In addition, Figure 4 It also shows that the PVDF adhesive has a larger oxidation and reduction peak current and peak area than the PVA adhesive, which indicates that the electrodes coated with different adhesives on the stainless steel foil surface not only affect the oxygen evolution potential and charging efficiency, but also affect the electrochemical activity of the manganese dioxide material and the charge and discharge redox reaction quantity.

[0162] Comparative Example 1

[0163] Take a 100*200mm, 50μm thick stainless steel foil, clean it with hot water containing a small amount of soda to remove oil stains, then ultrasonically clean it in an acetone solution for 5 to 10 minutes, wash it with clean water several times and blow it dry without any coating on the surface; cut the above-mentioned stainless steel foil without any coating into a size of 30×50 mm as an electrode current collector for standby use.

[0164] The 400-mesh manganese dioxide powder was tested by XRD, and its physical phase was mainly alpha phase structure, such as Figure 3As shown. Take 4.1g of manganese dioxide powder and add 10.4g of a water phase mixture containing 2.4% graphene by mass concentration, and mix it ultrasonically for 30 minutes. Add 0.5g of artificial graphite for mechanical stirring and mixing. After stirring for 16 hours, add 10g of CMC adhesive containing 1.5% by mass concentration, and then ball mill for 8 hours (ball-to-material ratio 10:1, speed 300 rpm). After taking out the slurry and degassing, the slurry is coated on the above-mentioned stainless steel current collector, dried at room temperature for several hours and dried in an oven at 80 degrees, and then rolled with a biaxial roller to the required electrode thickness of about 0.1 mm, and the electrode ears are spot welded; the manganese dioxide active material loading is measured to be 3.5mg / cm 2 The total thickness of the electrode is 110 microns. The electrode sheet composition contains 82% manganese dioxide, 5% graphene, 10% artificial graphite and 3% CMC manganese dioxide electrode slurry.

[0165] Battery preparation and testing:

[0166] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as the separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, constant current charge and discharge tests were performed.

[0167] Test conditions: charge and discharge battery density is 100mA / g, discharge cut-off potential is 0.9V.

[0168] Fig. 9 This is the battery cycle curve obtained by testing under constant current charge and discharge conditions. It can be seen that the initial discharge capacity of the manganese dioxide electrode assembled into a battery with stainless steel foil without any coating as the electrode current collector is only 25.5 mAh / g. As the number of cycles increases, the discharge capacity gradually increases, but the discharge capacity is low and decreases rapidly. The cycle stability is also not ideal, the charging efficiency is low, and the performance deteriorates quickly.

[0169] Comparative Example 2

[0170] Preparation of stainless steel current collector:

[0171] Weigh 2.1 g of PVDF powder and add it to 30 mL of N-methylpyrrolidone (NMP) solvent, and mix thoroughly with magnetic stirring to obtain a PVDF solution. Add 1.4 g of graphite to the PVDF solution, stir for 5 h, and ball mill. The ball milling parameters are ball-to-material ratio 10:1, ball milling time 10 h, and rotation speed 250 RPM to obtain a mixed slurry. Place the mixed slurry in a low-pressure degassing tank for degassing and set aside.

[0172] The stainless steel foil current collector was cleaned with hot water containing a small amount of soda to remove oil stains, then ultrasonically cleaned in acetone solution for 10 minutes, washed with clean water several times and blown dry for use. A 100*200mm, 50μm thick stainless steel foil was cut, and the slurry was evenly coated on both sides of the steel foil with a controllable thickness coater, first slowly dried at room temperature and then under infrared light, and finally dried in a vacuum oven at 120 degrees to form a protective layer with a thickness of about 50μm.

[0173] 4.0g of manganese dioxide powder was added to 12.3g of a graphene aqueous phase mixture containing 2.4% by mass concentration through 400 mesh, and ultrasonically mixed for 30 minutes. 0.44g of artificial graphite was added for mechanical stirring and mixing. After stirring for 15 hours, 13.2g of a CMC binder containing 1.5% by mass concentration was added, and then ball milled for 8 hours (ball-to-material ratio 10:1, speed 250 rpm). After taking out the slurry and degassing, the slurry was coated on the above-mentioned stainless steel current collector, dried at room temperature for several hours and dried in an oven at 80 degrees, and then rolled with a biaxial roller to the required electrode thickness of about 0.1 mm, and the electrode ears were spot welded; the manganese dioxide active material loading was measured to be 3.1mg / cm 2 The total thickness of the electrode is 100 microns. The electrode sheet composition contains 81% manganese dioxide, 6% graphene, 9% artificial graphite and 4% CMC manganese dioxide electrode slurry.

[0174] Battery preparation and testing:

[0175] A 0.3 mm thick zinc sheet was used as the negative electrode, and a membrane made of grafted polypropylene film and non-woven fabric was used as a separator between the manganese dioxide positive electrode and the zinc negative electrode. 1M MnSO4+1.5M ZnSO4 containing a trace amount of H2SO4 was used as the electrolyte (pH value was 4). After assembling the square battery, a constant current charge and discharge test was performed. Test conditions: the charge and discharge battery density was 100mA / g, and the discharge cut-off potential was 0.9V. The results show that the surface coating of the current collector has a certain degree of protection against electrolyte corrosion. However, the discharge capacity and cycle stability of the electrode are not ideal, and the performance deteriorates quickly.

[0176] In this comparative example, due to the large amount of adhesive added, the conductive performance of the protective coating is reduced; and since the relevant treatment process is not adopted, the protective coating fails to form a dense structure and has no anti-corrosion effect or has a poor anti-corrosion effect.

[0177] Table 1 Electrochemical performance of manganese dioxide positive electrode in examples and comparative examples

[0178]

[0179] *Performance of 30 cycles

[0180] The surface of the stainless steel current collector treated with a protective coating shows that the electrode treated with a mixture of conductive graphite and non-hydrophilic binder PVDF (Example 1) has the highest oxygen evolution potential, the best charge and discharge cycle stability and discharge capacity retention rate.

[0181] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A stainless steel current collector, characterized in that: The current collector has a three-layer sandwich structure, which includes a first protective coating, a stainless steel foil, and a second protective coating from top to bottom; The first protective coating and the second protective coating are both composed of a polymer binder and a conductive raw material, wherein the mass percentage of the polymer binder is 1 to 20%, and the mass percentage of the conductive raw material is 80 to 99%; wherein the first protective coating and the second protective coating both have a dense structure; The polymer adhesive is one of CMC, PVA or PVDF; The conductive raw material is one of graphite, graphene or carbon nanotubes; The thickness of the first protective coating and / or the second protective coating is 20-50 μm; the porosity of the first protective coating and the second protective coating is ≤5%; The method for preparing the current collector comprises the following steps: S1: weighing a polymer adhesive and a conductive raw material according to a preset ratio, and mixing and stirring the adhesive and an appropriate amount of solvent to obtain an adhesive solution; S2: adding the conductive raw material to the binder solution, stirring and ball milling to obtain a mixed slurry, and degassing the mixed slurry for later use; S3: Degreasing, cleaning and drying the stainless steel foil for later use; S4: coating the degassed mixed slurry on both sides of the stainless steel foil, and drying to obtain a stainless steel current collector having a first protective coating and a second protective coating; The specific parameters of the ball milling in step S2 are a ball-to-material ratio of 10:1, a rotation speed of 200-300 RPM, and a time of 2-6 hours, so that the binder and the conductive material are fully mixed and evenly ground into particles of smaller size, with a particle size distribution of 5-15 microns; The specific operation of degassing in step S2 is to place the slurry in a low-pressure degassing tank for degassing treatment to prevent pinholes from forming in the coating; The specific operation of step S3 is to soak the stainless steel foil in a sodium carbonate solution at 60-70°C for degreasing overnight, then rinse it with clean water and ultrasonically clean it in an acetone solution for 5-10 minutes, then rinse it with clean water and blow dry it for later use; The specific operation of drying in step S4 is to slowly dry the semi-finished stainless steel current collector under an infrared lamp and dry it in a vacuum oven at 100-150 degrees to solidify the protective coating.

2. A method for preparing the stainless steel current collector according to claim 1, characterized in that: The following steps are involved: S1: weighing a polymer adhesive and a conductive raw material according to a preset ratio, and mixing and stirring the adhesive and an appropriate amount of solvent to obtain an adhesive solution; S2: adding the conductive raw material to the binder solution, stirring and ball milling to obtain a mixed slurry, and degassing the mixed slurry for later use; S3: Degreasing, cleaning and drying the stainless steel foil for later use; S4: coating the degassed mixed slurry on both sides of the stainless steel foil, and drying to obtain a stainless steel current collector having a first protective coating and a second protective coating; The specific parameters of the ball milling in step S2 are a ball-to-material ratio of 10:1, a rotation speed of 200-300 RPM, and a time of 2-6 hours, so that the binder and the conductive material are fully mixed and evenly ground into particles of smaller size, with a particle size distribution of 5-15 microns; The specific operation of degassing in step S2 is to place the slurry in a low-pressure degassing tank for degassing treatment to prevent pinholes from forming in the coating; The specific operation of step S3 is to soak the stainless steel foil in a sodium carbonate solution at 60-70°C for degreasing overnight, then rinse it with clean water and ultrasonically clean it in an acetone solution for 5-10 minutes, then rinse it with clean water and blow dry it for later use; The specific operation of drying in step S4 is to slowly dry the semi-finished stainless steel current collector under an infrared lamp and dry it in a vacuum oven at 100-150 degrees to solidify the protective coating.

3. An electrode sheet, characterized in that: The electrode sheet comprises the stainless steel current collector according to claim 1 or the stainless steel current collector prepared by the preparation method according to claim 2.

4. The electrode sheet according to claim 3, characterized in that: The electrode sheet is composed of a stainless steel current collector and active materials, which are respectively a first active material layer, a stainless steel current collector, and a second active material layer from top to bottom; the specific composition of the active material is 80-82% manganese dioxide, 5-10% first conductive agent, 7-10% second conductive agent, and 3-5% binder in terms of mass percentage.

5. The electrode sheet according to claim 4, characterized in that: The first conductive agent is graphene or carbon nanotube; the second conductive agent is artificial or natural graphite; and the binder is CMC or PTFE.

6. A method for preparing an electrode sheet according to any one of claims 3 to 5, characterized in that: The following steps are involved: S21: weighing or measuring manganese dioxide powder, a first conductive agent, a second conductive agent and a binder according to a preset ratio, preparing a first conductive agent aqueous solution, and sieving the manganese dioxide powder and mixing and stirring the first conductive agent aqueous solution, and then performing ultrasonic crushing and mixing treatment; S22: preparing a binder solution, adding the second conductive agent and the binder solution to the mixed solution obtained in S21, stirring evenly and then ball milling to obtain a mixed slurry and degassing; S23: coating the mixed slurry on both sides of a stainless steel current collector having a protective layer and drying it, and rolling it to a desired thickness to obtain an electrode sheet.

7. A battery, characterized in that: The battery comprises the electrode sheet according to any one of claims 3 to 5 or the electrode sheet prepared by the preparation method according to claim 6.

Citation Information

Patent Citations

  • Current collector and preparation method thereof

    CN102593464A

  • Preparation method of graphene sheet modified spinel type lithium manganate or alpha type manganese dioxide electrode

    CN103198935A

  • Current collector and preparation method thereof

    CN106328953A

  • Metal / carbon composite current collector material and preparation method thereof

    CN106876716A